2015
DOI: 10.1002/adem.201500064
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Carbon Content on the Crystallization and Oxidation Behavior of Polymer‐Derived Silicon Carbide (SiC)

Abstract: Silicon Carbide (SiC) samples with controlled carbon contents are manufactured from polymeric precursors. Based on X-ray diffraction (XRD) data, a correlation of the excess carbon content and the crystallization kinetics of silicon carbide are determined for the obtained pyrolysates. The crystallization mechanisms as well as the corresponding activation energies E A are also determined. Furthermore, the influence of the carbon content on the oxidation behavior of these pyrolysates is studied. A model for the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Silicon carbide (SiC), as a conventional wide band gap semiconductor, has been widely implemented in high-temperature semiconducting devices 25,26 and graphene growth substrates, 27,28 due to its low thermal expansion coefficient, chemical inertness, and mechanical durability. In terms of LIB applications, unfortunately, SiC was traditionally considered to be electrochemically inert, 29,30 such that it has been mainly used as a structural reinforcement agent to couple with highcapacity materials such as Si and SnO 2 for forming composite anodes.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Silicon carbide (SiC), as a conventional wide band gap semiconductor, has been widely implemented in high-temperature semiconducting devices 25,26 and graphene growth substrates, 27,28 due to its low thermal expansion coefficient, chemical inertness, and mechanical durability. In terms of LIB applications, unfortunately, SiC was traditionally considered to be electrochemically inert, 29,30 such that it has been mainly used as a structural reinforcement agent to couple with highcapacity materials such as Si and SnO 2 for forming composite anodes.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Silicon carbide (SiC), as a conventional wide band gap semiconductor, has been widely implemented in high-temperature semiconducting devices , and graphene growth substrates, , due to its low thermal expansion coefficient, chemical inertness, and mechanical durability. In terms of LIB applications, unfortunately, SiC was traditionally considered to be electrochemically inert, , such that it has been mainly used as a structural reinforcement agent to couple with high-capacity materials such as Si and SnO 2 for forming composite anodes. Thanks to the recent extensive research in Si-based anodes, a number of studies have shown that lithium ions can intercalate into the lattices of SiC upon appropriate structural design and surface modification, suggesting that SiC could be electrochemically active toward lithium storage.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] Therefore, a wide range of SiC-based microsensing/electronics devices have been developed with several micromachining techniques. [7,8] Unlike silicon counterparts, SiC micromachining processes are undoubtedly limited and expensive due to the chemical inertness of SiC. For instance, SiC wet-etching processes typically requires extreme conditions and aggressive chemicals.…”
Section: Introductionmentioning
confidence: 99%
“…The advantages result from the high energy bandgap, mechanical strength, chemical inertness, and the high melting point of SiC . Therefore, a wide range of SiC‐based microsensing/electronics devices have been developed with several micromachining techniques . Unlike silicon counterparts, SiC micromachining processes are undoubtedly limited and expensive due to the chemical inertness of SiC.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] Silicon carbide finds applications in high power electronics (e.g., Schottky diode, transistors) and sensing devices including flame detection, gas sensing, thermal based sensors, and pressure sensors. [6][7][8][9] In addition, owing to the corrosive tolerance and mechanical robustness, SiC has also been utilized as a coating layer to improve the wear resistance of devices and instruments. [10,11] Among more than 200 types of SiC crystals, cubic silicon carbide, which can be epitaxially grown on Si substrates, has attracted great attention.…”
Section: Introductionmentioning
confidence: 99%